Temperature dependence of production of structured triacylglycerols in the alga Trachydiscus minutus - Řezanka, Tomáš; Lukavský, Jaromír; Sigler, Karel; Nedbalová, Linda; Vítová, Milada (Phytochemistry, 2015)
This study describes the identification of regioisomers and enantiomers of triacylglycerols of C20 polyunsaturated fatty acids (PUFAs) in the alga Trachydiscus minutus cultivated at different temperatures using reversed- and chiral-phase liquid chromatography-mass spectrometry. The use of the two different phases contributes to ready identification, both qualitative and semiquantitative, of regioisomers and enantiomers of triacylglycerols containing eicosapentaenoic and arachidonic in the molecule. The ratio of regioisomers and enantiomers of triacylglycerols (TAG) depends on the temperature of cultivation; with lowering temperature the proportion of the achiral TAG increases and the enantiomer ratio diverges from 1:1.
Keywords: triglyceridy; Heterokontophyta; Temperature; Triglycerides; Stramenopiles; Eustigmatophyceae; Alga; Chiral-LC/APCI-MS; Structured triacylglycerols; teplota; nenasycené mastné kyseliny; Stereoisomerism; stereoizomerie; Fatty Acids, Unsaturated; Trachydiscus minutus